The Australian Trauma Registry - Fitzgerald, Mark C. (ANZ J Surg, 2018)
INTRODUCTION: Injuries are a major cause of disability and lost productivity. The case for a national trauma registry has been recognized by the Australian Commission on Safety and Quality in Health Care and at a policy level. BACKGROUND: The need was flagged in 1993 by the Royal Australasian College of Surgeons and the Australasian Trauma Society. In 2003, the Centre of National Research and Disability funded the Australian and New Zealand National Trauma Registry Consortium, which produced three consecutive annual reports. The bi‐national trauma minimum dataset was also developed during this time. Operations were suspended thereafter. METHOD: In response to sustained lobbying the Australian Trauma Quality Improvement Program including the Australian Trauma Registry (ATR) commenced in 2012, with data collection from 26 major trauma centres. An inaugural report was released in late 2014. RESULT: The Federal Government provided funding in December 2016 enabling the work of the ATR to continue. Data are currently being collected for cases that meet inclusion criteria with dates of injury in the 2017–2018 financial year. Since implementation, the number of submitted records has been increased from fewer than 7000 per year to over 8000 as completeness has improved. Four reports have been released and are available to stakeholders. CONCLUSION: The commitment shown by the College, other organizations and individuals to the vision of a national trauma registry has been consistent since 1993. The ATR is now well placed to improve the care of injured people.